A06 Better global and cognitive functioning for choreatic compared to hypokinetic-rigid huntington's disease. (29th August 2012) - 't Hart, E; Marinus, H; Burgunder, JM; Bentivoglio, AR; Craufurd, D; Reilmann, R; Saft, C; Roos, R; ,
Abstract : Background: Motor disturbances in Huntington's disease can be subdivided into a predominantly choreatic or hypokinetic-rigid subtype. The relation between these motor subtypes and cognitive and general functioning is poorly understood, but can be of importance in the care for Huntington's disease patients. Aims: Investigating the possible clinical differences between predominantly choreatic and predominantly hypokinetic-rigid Huntington's disease. Methods/technique: Cross-sectional data from the European Huntington's Disease Network Registry study up until 2011 were analysed. Data of the first visit of all subjects with an expanded CAG ≥36 and a total motor score ≥5 and complete cognitive, function and motor assessments were retrieved. A total of 1882 subjects were classified as predominantly choreatic (N=528) or predominantly hypokinetic-rigid (N=432), according to their score on those items of the total motor score a priori labelled as either choreatic or hypokinetic-rigid items; the other 922 patients were of a mixed motor type. The relationship between motor type and cognitive (total cognitive score) and general functioning (total functional capacity) was investigated using a linear regression model. Results/outcome: Motor subtype was a significant predictor of both cognitive and general functioning (p<0.001). In both analyses the patients with the choreatic type had significantly better scores than those with the hypokinetic-rigid type. The total amount of variance explained by the cognitive model is 58% and by the general functioning model 56% (p<0.001). In both models motor subtype was the second most influential predictor (p<0.05). Conclusions: We conclude that Huntington's disease patients with a predominant choreatic motor phenotype exhibit better global and cognitive functioning than patients with a predominant hypokinetic-rigid motor phenotype.